Ernest Hemingway : A Comprehensive Bibliography - Hanneman, Audre (Book collections on Project MUSE., 2015)
This bibliography of Hemingway's writings and related materials includes, for the first time, all of his books, pamphlets, stories, articles, newspaper contributions, juvenilia, library holdings of his letters and manuscripts, items written about Hemingway between 1918 and 1965, and short excerpts from reviews of each of Hemingway's novels. It is the first bibliography of Hemingway published since 1931, and includes much material never before assembled: thirty-eight contributions to his high school newspaper, Trapeze, twenty-eight Spanish Civil War dispatches, and first editions published in some thirty foreign languages. First editions of books and pamphlets, both American and English with bibliographic descriptions, are given.Originally published in 1967.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.